Optimizing aortic arch branch cannulation in acute type A dissection surgery: a minimally invasive approach - Lin Xia; Ying Lyu; Xiong Xiao; Zhonglu Yang; Yuguang Ge; Bin Wang; Yu Liu; Hui Jiang (Frontiers in Cardiovascular Medicine)
BackgroundThe optimal cannulation strategy for acute type A aortic dissection (ATAAD) surgery via a minimally invasive approach remains a topic of debate. This study aimed to compare the feasibility and safety of different aortic arch branch cannulation techniques using a single upper hemisternotomy.MethodsA retrospective analysis was performed on 207 patients with ATAAD who underwent total arch replacement combined with frozen elephant trunk techniques between December 2019 and July 2023. Patients were categorized into four groups based on the cannulation site: IA group (innominate artery, n = 174), LCA group (left carotid artery, n = 21), RSA group (right subclavian artery, n = 5), and RCA group (right carotid artery, n = 7). Perioperative outcomes, including mortality, complications, and operative times, were compared using appropriate statistical methods.ResultsA total of 207 patients were included and categorized into four groups based on the site of arterial cannulation: IA (n = 174), LCA (n = 21), RSA (n = 5), and RCA (n = 7). Baseline characteristics, including age and preoperative comorbidities, were comparable across the groups. Intraoperative metrics, such as cross-clamp time, circulatory arrest time, selective cerebral perfusion time, and cardiopulmonary bypass (CPB) time, showed no statistically significant differences. Although the CPB time was numerically shorter in the IA group, this difference was not significant (p > 0.05). Perioperative mortality occurred in 25 patients (12.1%), with no statistically significant differences among the groups (IA: 12.6%, LCA: 0%, RSA: 20.0%, RCA: 28.6%; p > 0.05). Postoperative clinical outcomes, including ventilator support duration, ICU stay, and hospital length of stay, were also similar across all groups.ConclusionAortic arch branch cannulation is a feasible and safe arterial perfusion strategy for ATAAD surgery via a minimally invasive single upper hemisternotomy. Among the options, the innominate artery demonstrated favorable outcomes and was not inferior to other arch vessels, and may be considered a suitable first choice when feasible.